Legal Responsibilities of Independent Practice Midwives in Implementing Reference as an Effort to Save Mothers and Babies in Sukamara Regency, Kalimantan Province - Mahalia Mahalia; Marcella Elwina; Hadi sulistiyanto (Soepra Jurnal Hukum Kesehatan, 2022)
Abstract: Midwifery referrals are services provided by midwives in the context of making referrals to a higher service system or vice versa, namely services provided by midwives when receiving referrals from traditional birth attendants who help deliveries, as well as referral services conducted by midwives to other health service places / facilities. horizontally or vertically to other health professions. Proper midwifery services will improve the safety and well-being of mothers and their babies. Referral is made if there are certain conditions such as personnel and equipment in a health facility unable to manage complications that may occur.This research is asociological juridical research with analytical descriptive specifications. The data used in this research is primary data which is mainly obtained from interviews and secondary data obtained from literature studies. The data analysis method used is a qualitative method.From the results of thestudy it can be shown that in general the midwives in Sukamara Regency have understood their responsibilities in making referrals by following the flow and rules that apply in the individual health referral system stipulated in the Minister of Health Regulation Number 001 of 2012 concerning the Individual Health Care Referral System and System Guidelines. National Reference. However, the results of the study also showed that the mortality rate for mothers and babies in Sukamara District was still quite high. This is due to various conditions including delays in referring emergency patients to health facilities, local cultural factors, infrastructure, and difficult geographical conditions. Midwives are health workers, so the reference to the legal responsibility of midwives is referred to mainly from Law Number 36 of 2009 concerning Health, Law Number 4 of 2019 concerning Midwifery. From a legal perspective, the health professionals, including midwives, can be held accountable according to the rules in civil law, criminal law and administrative law. Midwives can also be subject to ethical sanctions based on the professional code of ethics of midwives.The suggestions or recommendations given by the author in relation to the results of the research are for midwives and other health workers so that they can provide health services to patients based on science and are guided by laws and regulations, professional service standards, standard operating procedures and code of ethics related to duties and authority. to maintain the quality of health services and always strive to improve competence by attending trainings.Keywords:    legal responsibility, referral, efforts to save mothers and babies, independent practicing midwives